The methodology of law enforcement policy - M. Kleymenov; D. Erokhin (Правоприменение)
The subject of the paper is methodology of law enforcement policy, elements and relevance for law enforcement activity.The main aim of the paper is to confirm or disprove the hypothesis that methodology of law enforcement policy is a system of intellective elements and a part of the higher level system of law enforcement policy simultaneously.The description of methodology. The methodological basis of research is systematic approach. Authors analyze the methodology of law enforcement policy as a combination of elements influencing on each other. The dialectic and formal-legal methodology is also used when the authors analyze trends in judicial practice.The main results and scope of their application. Law enforcement policy is a state strategy that defines the main directions, methods and means of implementation of legal regulations. From the standpoint of a systematic approach, law enforcement policy is a system of managerial type that consists of three elements: subject, object and means (methods). The methodology of law enforcement is a system of interacting elements, such as: modeling the main directions of the implementation of the law; specification of the general strategy for the implementation of legal regulations; identifying trends in law enforcement; correction of law enforcement practices; scientific and methodological support of law enforcement policy. The authors analyze each of the listed elements of the law enforcement policy, pointing out their role in improving the practice of law enforcement. The proposed analysis may become a crucial point for research in the field of law enforcement methodology. The results of research may be used as the basis of correction of methodology of law enforcement practice.